18F-FAPI-04 PET/CT in the evaluation of ground-glass nodules less than 3 cm in diameter comparing to 18F-FDG PET/CT - Lyu, Zhehao; Liu, Jianing; Han, Wei; Guo, Shibo; Duan, Chunyu; Liu, Lili; Zhao, Hongyue; Su, Yexin; Wang, Haibo; Zhang, Qi; Tian, Lin; Fu, Peng (Frontiers in Oncology, 2025)
BackgroundThis study aimed to evaluate the clinical usefulness of fluorine 18F−FAPI-04 PET/CT in diagnosing ground-glass nodules that are less than 3 cm in diameter in comparison with fluorine 18F-FDG PET/CT.MethodsProspective analysis of 18F-FAPI-04 PET/CT and 18F-FDG PET/CT scans for 74 patients with 96 GGNs less than 3 cm from 09/2021 to 10/2024 were analyzed. 18F-FAPI-04 imaging was performed in patients with 18F-FDG PET/CT within a week. The images, parameters, and histopathological invasiveness from participants were analyzed. Tumor uptake was quantified by the maximum standard uptake value (SUVmax), standard uptake value mean (SUVmean), target-to-background ratio (TBR), and the ratio of SUVmax of the lesion to SUVmax of contralateral normal lung parenchyma (SUVindex).ResultsA total of 74 patients with 96 GGNs were evaluated. Different pathological subtypes of GGNs exhibited distinct uptake values on 18F-FAPI-04 and 18F-FDG PET/CT. The invasive pathological subtypes showed higher uptakes than noninvasive subtypes, of which 18F-FAPI-04 PET/CT showed significantly higher uptake than 18F-FDG PET/CT in all subtypes of GGNs (all P<0.05). Notably, the optimal cut-off values for specificity of SUVmax, SUVmean, SUVindex, and TBR of 18F-FAPI-04 PET/CT were notably higher than those of 18F-FDG PET/CT.Conclusion18F-FAPI-04 PET/CT is useful for detecting GGNs, outperforming 18F-FDG PET/CT in detecting their invasiveness. It could provide valuable guidance for early-stage adenocarcinoma diagnosis, potentially impacting patient management.Trial registrationChinese Clinical Trial Registry, ChiCTR2100051406. Registered 23 September 2021 ‘Retrospectively registered’, https://www.chictr.org.cn/showproj.html?proj=133033